A Facile Synthesis of Raltegravir Potassium—An HIV Integrase Inhibitor. (14th August 2019) - Karumanchi, Kishore; Nangi, Gangadhara Bhima Shankar; Danda, Subba Reddy; Chavakula, Ramadas; Korupolu, Raghu Babu; Bonige, Kishore Babu
Abstract : A facile, cost‐effective, and commercially viable synthesis of Raltegravir Potassium (1 ) has been developed from 2‐(1‐amino‐1‐methyl‐ethyl)‐ N ‐[(4‐fluorophenyl)methyl]‐1, 6‐dihydro‐5‐hydroxy‐1‐methyl‐6‐oxo‐4‐pyrimidinecarboxamide (9 ) with high purity and in good yields. In addition, a new approach for the synthesis of key amine intermediate (9 ) of Raltegravir Potassium (1 ) from commercially available 2‐amino‐2‐methylpropanenitrile hydrochloride (2 ) is also described. The key features of the synthesis are fewer synthetic steps, employing the inexpensive reagents and eco‐friendly. Abstract :